Endoplasmic reticulum stress associates with the development of intervertebral disc degeneration - Huang, Jishang; Zhou, Qingluo; Ren, Qun; Luo, Liliang; Ji, Guanglin; Zheng, Tiansheng (Frontiers in Endocrinology, 2023)
Endoplasmic reticulum (ER) is an important player in various intracellular signaling pathways that regulate cellular functions in many diseases. Intervertebral disc degeneration (IDD), an age-related degenerative disease, is one of the main clinical causes of low back pain. Although the pathological development of IDD is far from being fully elucidated, many studies have been shown that ER stress (ERS) is involved in IDD development and regulates various processes, such as inflammation, cellular senescence and apoptosis, excessive mechanical loading, metabolic disturbances, oxidative stress, calcium homeostasis imbalance, and extracellular matrix (ECM) dysregulation. This review summarizes the formation of ERS and the potential link between ERS and IDD development. ERS can be a promising new therapeutic target for the clinical management of IDD.